Process for the preparation of thienamycin and intermediates - RATCLIFFE; RONALD W; CHRISTENSEN; BURTON G; SALZMANN; THOMAS N (1986)
In a process for the total synthesis of thienamycin from L-aspartic acid via intermediate III: III R=H, blocking group or salt cation there is disclosed a process for preparing III via wherein R is a protecting group.